Symposium on Dru Johnson’s Biblical Philosophy - Austin, Michael W. (Philosophia Christi, 2024)
In this paper, I introduce the symposium on Dru Johnson’s Biblical Philosophy: A Hebraic Approach to the Old and New Testaments. I discuss the aims of the book and offer an example of how Johnson’s insights can be applied to a perennial philosophical problem, namely, the nature of truth. I then offer some suggestions for applying its contents to our philosophizing today. Finally, I briefly introduce each contribution to the symposium that follows.